The effect of NPK 16-6-23 fertilizer dosage on the growth and yield of the rice Inpari 30 in Bangkalan regency, East Java - Lina Aisyawati; Fuad Nur Aziz; Winda Syafitri; Ratih Kusumasari Ndaru; Evy Latifa (The East Java Biological Society, 2020)
Comprehensive site-specific fertilization dose is an essential factor to increase crop production. Fertilizer dose application should be based on the nutrient content in soil and plant, type and quality of fertilizer, and the climate. This study was aimed to determine the effect of unbalanced compound fertilizer NPK 16-6-23 at various doses to rice crops’ growth and yield Inpari 30 in Bangkalan regency. This research was conducted from June to October 2016. The rice varieties were Inpari 30 planted with legowo 2: 1 row system. The study used 8 different treatments : (1) without fertilizer, (2) standard dose of 200 kg/ha Urea and 300 kg/ha NPK 15-15-15, (3) 200 kg/ha NPK 16-6-23, (4) 300 kg/ha NPK 16-6-23, (5) 400 kg/ha NPK 16-6-23, (6) 200 kg/ha Urea + 200 kg/ha NPK 16-6-23, (7) 200 kg/ha Urea + 300 kg/ha NPK 16-6-23, and (8) 100 kg/ha Urea + 400 kg/ha NPK 16-6-23. The study used a randomized complete block design with 3 replications. The parameters were observed by plant height, number of productive tillers, panicle length, number of grain per panicle, number of filled and empty grain per panicle, percentage of filled grain, 1000 seed weight, and productivity. The results showed that 200 kg/ha Urea + 300kg/ha NPK 16-6-23 produced the highest plant growth on 50 DAP (77.83 cm), a low number of empty grain (11.84), a high percentage of filled grain (90.7%), and high production (7.29 t/ha). This treatment has agronomically higher effectiveness compared to standard doses with RAE value of 196.61%. This fertilizer dose is highly recommended for farmers to increase Inpari 30 rice crops in Bangkalan.